Peningkatan Kualitas Lulusan melalui Integrasi Kurikulum Model Jaringan (Networked Model) di Madrasah Tsanawiyah dan Madrasah Aliyah Cirebon - Yusuf; Karmila, Wati (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study aims to analyze efforts to improve graduate quality through the integration of the Networked Model curriculum at Madrasah Tsanawiyah Negeri and Madrasah Aliyah Negeri Babakan Ciwaringin, Cirebon. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and curriculum document analysis, and were thematically analyzed using the CIPP evaluation framework (Context, Input, Process, Product). The findings indicate that the madrasahs possess contextual strengths in the form of a religious academic culture, strong internal teacher capacity, and institutional networks that support curriculum integration. However, a gap was identified between administratively driven curriculum policies and organically developed networked integration practices at the instructional level. Curriculum evaluation tends to focus on the fulfillment of formal indicators and has not been optimally utilized as a basis for reflective practice and strategic decision-making. This study concludes that improving the quality of madrasah graduates requires the strengthening of reflective, adaptive, and contextual curriculum evaluation to ensure that madrasah strengths can be managed sustainably.